Femtosecond laser–assisted capsulotomy with capsular marks for toric IOL alignment: Comparison of tensile strength with standard femtosecond laser capsulotomy. Issue 8 (August 2019) - Teuma, Valas E.; Gray, Gary; Bedi, Raman; Packer, Mark
Abstract : Purpose : To compare the capsulotomy rim strength with capsular marks (CMs) to the rim strength without CMs in porcine eyes, and to demonstrate the practicality of CMs for intraoperative toric intraocular lens (IOL) alignment. Setting : LENSAR facility, Orlando, Florida, USA. Design : Laboratory study. Methods : The biomechanical strength of the capsulotomy with CMs was tested under two different load orientations (orthogonal to or in‐line with CMs). Thirty‐six porcine eyes were randomly assigned to three treatment cohorts: (1) standard capsulotomy with no CMs, (2) capsulotomy with CMs for in‐line tensile testing and (3) capsulotomy with CMs for orthogonal tensile testing. Study parameters were capsulotomy break force and maximum extensibility. The ease of using CMs for toric IOL alignment was also evaluated. Results : There was no significant difference between the mean break force for standard capsulotomy (180.57 mN ± 22 [SD]), capsulotomy with CMs with orthogonal load (178.04 ± 20 mN, P = 1.000), and with in‐line load (181.05 ± 15 mN, P = 1.000). Likewise, the mean extensibility at the break point for standard capsulotomy (6.47 ± 0.33 mm) was equivalent to the mean extensibility with CMs with orthogonal load (6.49 ± 0.45 mm, P = 1.000) and with in‐line load (6.3 ± 0.47 mm, P = .960). In the implanted eyes, toric IOLs were found to be easily aligned with the CMs. Conclusion : The femtosecond laser capsulotomies with CMs were equivalent in tensile strength and extensibility to standard femtosecond laser capsulotomies and showed high potential for effective alignment of toric IOLs.